A caffeine-supplemented diet modulates oxidative stress markers and prevents oxidative damage in the livers of Nile tilapia (Oreochromis niloticus) exposed to hypoxia - Baldissera M.D. (2019)
© 2019, Springer Nature B.V.Recent evidence has revealed the involvement of oxidative stress and oxidative damage with health impairment and mortality in fish exposed to hypoxia. Thus, natural compounds with antioxidant and free-radical-scavenging properties, such as caffeine, might help to prevent or reduce hepatic damage elicited by hypoxia. Thus, the aim of this study was to evaluate whether dietary supplementation with caffeine could prevent or reduce oxidative damage in the livers of Nile tilapia (Oreochromis niloticus) exposed to hypoxia. Hepatic reactive oxygen species, lipid peroxidation levels, and xanthine oxidase (XO) activity were higher in fish exposed to hypoxia compared with normoxia. Hepatic catalase, glutathione peroxidase, and glutathione S-transferase activities, as well as the antioxidant capacity against peroxyl radical levels, were lower in fish exposed to hypoxia compared with normoxia. No significant difference between groups was observed regarding hepatic superoxide dismutase activity. Dietary supplementation with 8% caffeine prevented all alterations elicited by hypoxia. Based on this evidence, the use of dietary supplementation with 8% caffeine can be an interesting approach to preventing hepatic lipid damage and impairment of the antioxidant defense system elicited by hypoxia, and this effect can be mediated by protective effects on XO activity.